The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.sjbs.2015.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating agro-industrial by-products as dietary roughage source on growth performance of fattening steers

Abstract: Silages from pineapple peel, sweet corn husk and cob mixed with bagasse and vinasse were evaluated to determine their chemical composition and fermentation characteristics as well as feeding performance in fattening steers. The experiment, which lasted 90 days, involved 48 fattening steers (264 ± 37.4 kg BW) randomly allocated to three diets. Treatments included: a control diet containing rice straw and molasses (T1); diet containing bagasse-vinasse mixture including sweet corn husk and cob silage (BS; T2); an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 18 publications
5
16
0
1
Order By: Relevance
“…Kemenade, den Hartog, Haaksma, and Verstegen (1988) obtained similar results which showed the feed intake of bull calves and broilers increases by vinasse addition and this consequently causes a greater average daily weight gain in these animals (Kemenade et al, 1988). But Maneerat, Prasanpanich, Tumwasorn, Laudadio, and Tufarelli (2015) have shown reduction in feed intake in steers fed by bassagevinasse compared with molasses. Also, Zali, Eftekhari, Fatehi, and Ganjkhanlou (2017) have reported higher live slaughter weight in Holstein male calves fed with diet containing 5% vinasse.…”
Section: Discussionmentioning
confidence: 95%
“…Kemenade, den Hartog, Haaksma, and Verstegen (1988) obtained similar results which showed the feed intake of bull calves and broilers increases by vinasse addition and this consequently causes a greater average daily weight gain in these animals (Kemenade et al, 1988). But Maneerat, Prasanpanich, Tumwasorn, Laudadio, and Tufarelli (2015) have shown reduction in feed intake in steers fed by bassagevinasse compared with molasses. Also, Zali, Eftekhari, Fatehi, and Ganjkhanlou (2017) have reported higher live slaughter weight in Holstein male calves fed with diet containing 5% vinasse.…”
Section: Discussionmentioning
confidence: 95%
“…Thus Holstein steers fed pTMR diet received a more high-energy diet than steers fed nTMR and cTMR. Accordingly, Maneerat et al (2015) found that steers (Brahman × Thai) fed pineapple peel silage mixed with bagasse and vinasse (BP) exhibited the highest ADG level related to the NFE and gross energy of pineapple silage compared with sweet corn silage. Although CP in the pTMR diet was lower than in the cTMR diet, the levels of CP in the TMR diets had no effect on growth performance in the feedlot stage (Boonsaen et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, researchers have focused on the performance and the apparent digestibility of pineapple byproduct when used as feed. Previous studies reported that Brahman × Thai steers fed silage from pineapple peel mixed with bagasse and vinasse led to increased gross energy and a higher average daily gain (ADG) compared with sweet corn husks and cob silage mixed with bagasse and vinasse (Maneerat et al, 2015). Additionally, Zainuddin et al (2014) found that the by-product from pineapple stems contained high levels of crude fibre (CF) (average 39.75%) and carbohydrate (average 41.92%), but there was no report of feeding pineapple stems to feedlot cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Sheep fed with pineapple peel‐added silage during 90 days showed an increase in body weight, which suggested that pineapple peels might be an economically feasible agro‐industrial byproduct for farmers (Maneerat, Prasanpanich, Tumwasorn, Laudadio, & Tufarelli, ).…”
Section: Wastes and Byproducts From Tropical Fruits And Their Currentmentioning
confidence: 99%